Time variation in Okun's law: A Canada and US comparison - Kimberly Beaton (Bank of Canada, 2010)
This article investigates the stability of Okun's law for Canada and the United States using a time varying parameter approach. Time variation is modeled as driftless random walks and is estimated using the median unbiased estimator approach developed by Stock and Watson (1998). Okun's law exhibits structural instability in both countries, with the sensitivity of the unemployment rate to movements in output growth increasing recently over time in both Canada and the United States.
Keywords: E24; J00; 330; Business fluctuations and cycles; Labour markets; Konjunktur; Arbeitsmarkt; Arbeitslosigkeit; Okun's Law; USA; Kanada